Comparison and Evaluation of Current Animal Models for Perineural Scar Formation in Rat - O Zanjani, Leila (Mashhad University of Medical Sciences, 2013)
Objective (s): Scar formation in injured peripheral nerve bed causes several consequences which impede the process of nerve regeneration. Several animal models are used for scar induction in preclinical studies which target prevention and/or suppression of perineural scar. This study evaluates the translational capacity of four of physical injury models to induce scar formation around the sciatic nerve of rat: laceration, crush, mince and burn. Materials and Methods: Functional (Toe out angle), macroscopic, and microscopic evaluations were performed weekly for four weeks and correlation of findings were analyzed. Result: While macroscopic and microscopic findings suggested a well-developed and adhesive fibrosis surrounding the sciatic nerve, functional assessment did not reveal any significant difference between control and experimental groups (P>0.05). Conclusion: Our study suggests that none of the applied animal models reproduce all essential features of clinical perineural scar formation. Therefore, more studies are needed to develop optimal animal models for translating preclinical investigations.